Tourism Operator Sustainability Predictive Model in Marine Park - Mohamad, Zaleha; Ramli, Nurhafizah; Muslim, Aidy Mohamed Shawal M.; Hii, Yii Siang (International Review of Management and Marketing, 2017)
Sustainable tourism is the concept of visiting a place as a tourist and trying to make only a positive impact on the environment, society and economy. Tourism can involve primary transportation to the general location, local transportation, accommodations, entertainment, recreation, nourishment and shopping. In this context, the research study tourism is operator towards recreational. This study analyzed the sustainability tourism predictive model towards operator in marine park. The research addresses concentrating on four variables which are attractiveness, risks and hazards, maintenance and cleanliness and infrastructure. By using regression analysis, the result found that all four variables were predicted influences the sustainable tourism in marine park. Keywords: Tourism, operators, sustainability JEL Classifications: L83, Q55, Z32